Doping and intercalation synergy in BCN@CMC hybrids: Tailored band structure and stable ECG & EEG signal transduction - Raju, Spoorthi; Manjunathaswamy, Mohan Krishnaiahnahundi; Virupakshappa, Punyashree Kattebelaguli; Sangameshwar, Madhukar Beejaganahalli; Ningappa, Kumara Swamy; Shivarudraiah, Vedhavathi Hatna (Materials science & engineering. B, Solid-state materials for advanced technology, 2026)
2D Borocarbonitride (BCN) nanomaterials were synthesized by the sol-gel method, followed by the incorporation of BCN into the carboxymethyl cellulose (CMC) polymer matrix via the solution casting method, resulting in BCN@CMC nanocomposites with variable BCN concentration. A comprehensive characterization of synthesized nanoparticles and its nanocomposites was done by using different characterization XRD, FT-IR, SEM, TEM and UV–visible and photoluminescence. A notable reduction in the optical band gap was observed with increasing BCN content within the CMC matrix. The direct band gap energy decreased from 3.03 eV to 2.51 eV, while the indirect band gap dropped from 3.25 eV to 3.00 eV, and the nanocomposite is observed to exhibit characteristics of an indirect semiconductor. In particular, their utility was demonstrated in an ECG sensing system, where the AD8232 module and Arduino microcontroller were integrated with a BCN@CMC electrode exhibiting stable impedance characteristics, which are critical for acquiring high-fidelity ECG signals. Among the various formulations, electrodes fabricated with 1.0 wt% and 2.0 wt% BCN show optimal performance, highlighting their suitability for biomedical sensor applications. A three lead EEG system incorporating BCN@CMC electrodes was designed to monitor brain activity in both healthy and visually impaired subjects. The 2.0% BCN@CMC electrode demonstrated reliable detection of alpha and beta waves, performing comparably to conventional Ag/AgCl electrodes. Based on this, the developed BCN@CMC nanocomposite shows promising potential for applications in electrochemical systems, such as conductive sensors, optical devices. [Display omitted] •BCN nanoparticle are synthesized by the sol-gel method.•Incorporation of BCN into the CMC polymer matrix via the solution casting method.•The synthesized BCN@CMC nanocomposites exhibit potential for UV-blocking applications, as well as electrical dielectrical studies.•BCN@CMC nanocomposite exhibits strong potential for integration into ECG and EEG electrode systems for biomedical signal recording.